2015
DOI: 10.3390/biom5021035
|View full text |Cite
|
Sign up to set email alerts
|

Initial Events in Bacterial Transcription Initiation

Abstract: Transcription initiation is a highly regulated step of gene expression. Here, we discuss the series of large conformational changes set in motion by initial specific binding of bacterial RNA polymerase (RNAP) to promoter DNA and their relevance for regulation. Bending and wrapping of the upstream duplex facilitates bending of the downstream duplex into the active site cleft, nucleating opening of 13 bp in the cleft. The rate-determining opening step, driven by binding free energy, forms an unstable open comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
270
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 173 publications
(279 citation statements)
references
References 135 publications
(305 reference statements)
8
270
0
1
Order By: Relevance
“…Studies by Record and colleagues identified a series of λP R promoter complexes that differ in RNAP-DNA interactions, including two unstable open intermediates, I 2 and I 3 , and a very stable final open complex, RPo (19). During the isomerization from I 3 into RPo, RNAP tightens its interactions with NT DISC and the downstream duplex DNA regions, massively stabilizing the complex (2,19).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by Record and colleagues identified a series of λP R promoter complexes that differ in RNAP-DNA interactions, including two unstable open intermediates, I 2 and I 3 , and a very stable final open complex, RPo (19). During the isomerization from I 3 into RPo, RNAP tightens its interactions with NT DISC and the downstream duplex DNA regions, massively stabilizing the complex (2,19).…”
Section: Resultsmentioning
confidence: 99%
“…1). The mobile β′ clamp domain that forms one of the pincers stands out as a central regulatory feature (1,2). The open clamp likely allows the loading of the promoter DNA during initiation and the release of the template and the nascent RNA during termination.…”
mentioning
confidence: 99%
“…RNA polymerase | transcription start site selection | promoter | transcription bubble | transcription initiation T ranscription initiation consists of a number of biochemical steps leading to formation of a phosphodiester bond between a nucleoside triphosphate (NTP) bound in the RNA polymerase (RNAP) active-center initiating NTP binding site (i site) and an NTP bound in the RNAP active-center extending NTP binding site (i+1 site) (1)(2)(3). For bacterial RNAP, promoter-specific initiation requires the RNAP core enzyme (subunit composition α 2 ββ'ω) to associate with a σ factor forming the RNAP holoenzyme (subunit composition α 2 ββ'ωσ).…”
mentioning
confidence: 99%
“…coli RNA polymerase E. coli RNA polymerase holoenzyme σ70 is a sequencespecific DNA binding protein and specifically recognizes the −35 and −10 sequences of E. coli promoters to form a closed complex and then an open complex (Harley and Reynolds 1987;Ruff et al 2015). One critical event for RNA polymerases is to open or unwind the DNA molecule to initiate RNA synthesis de novo (Fisher 1982;Zuo and Steitz 2015).…”
Section: Bacterial Dna Replication Initiators: λ O and Dnaamentioning
confidence: 99%